2013
DOI: 10.1155/2013/192026
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Trace Elemental Analysis in Cancerous and Noncancerous Human Tissues Using PIXE

Abstract: The effect of high or low levels of trace metals in human tissues has been studied widely. There have been detectable significant variations in the concentrations of trace metals in normal and cancerous tissues suggesting that these variations could be a causative factor to various cancers. Even though essential trace metals play an important role such as stabilizers, enzyme cofactors, elements of structure, and essential elements for normal hormonal functions, their imbalanced toxic effects contribute to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 35 publications
3
25
0
4
Order By: Relevance
“…On the other side, the treated with Micromelum minutum seeds extract and its coumarin ingredient to diabetic rats increased p53 expression while decreased bcl-2 expression. These results were in agreement with that of Mulware [47] who reported that diabetes cause induction of oxidative-induced DNA damage by ROS may lead to isolated base lesions or single-strand breaks, complex lesions like double-strand breaks, and some oxidative generated clustered DNA lesions (OCDLs) which are linked to cell apoptosis and mutagenesis. On the other side, coumarin has anti-apoptotic activity, an inhibitor of p53 abrogated glucolipotoxicity-induced ROS generation and p53 expression [48].…”
Section: Discussionsupporting
confidence: 93%
“…On the other side, the treated with Micromelum minutum seeds extract and its coumarin ingredient to diabetic rats increased p53 expression while decreased bcl-2 expression. These results were in agreement with that of Mulware [47] who reported that diabetes cause induction of oxidative-induced DNA damage by ROS may lead to isolated base lesions or single-strand breaks, complex lesions like double-strand breaks, and some oxidative generated clustered DNA lesions (OCDLs) which are linked to cell apoptosis and mutagenesis. On the other side, coumarin has anti-apoptotic activity, an inhibitor of p53 abrogated glucolipotoxicity-induced ROS generation and p53 expression [48].…”
Section: Discussionsupporting
confidence: 93%
“…69 Moreover, high copper levels are considered carcinogenic, and are suspected to encourage tumour progression through the production of reactive oxygen species (ROS; for an in-depth review see 70 ). [71][72][73][74] [71][72][73][74] …”
Section: Copper and Its Link To Cancermentioning
confidence: 99%
“…Cancer cells appear to demonstrate both increased steady state levels of ROS (O 2 •- and H 2 O 2 ) and abnormal metabolism of transition metals when compared to normal cells [4, 35]. It has been shown that free and bound copper and iron concentrations are higher in breast compared to the normal surrounding tissue [9, 10, 36]. These metal ions participate in many critical biological functions however the same properties that allow for the gain or loss of electrons also results in cytotoxicity through the donation of electrons to oxygen, leading to the generation of highly toxic hydroxyl radicals and other ROS.…”
Section: Discussionmentioning
confidence: 99%
“…For example, breast and lung cancer patients contain elevated serum copper levels when compared to cancer-free patients [8]. Breast and lung tumors also contain markedly increased copper when compared to their matched normal tissue [9-11]. Labile iron concentrations are also increased in both serum and tumor tissue from cancer patients [12].…”
Section: Introductionmentioning
confidence: 99%